The effect of loyalty programmes on customer loyalty in the retail banking sector in South Africa - Olifant, Daniella (University of the Witwatersrand, Johannesburg, 2021)
It is estimated that there are more than 100 loyalty programmes in operation in South Africa, with retail programmes dominating the loyalty landscape. However the banking sector has seen many of its banks embark on this journey and introduce loyalty programmes as part of their service offering. While there has been a great amount of research on loyalty programmes, little has been done to see if indeed a loyalty programme, in the traditional sense, has resulted in customer retention and loyalty in the banking sector. This study therefore examines the effect of loyalty programmes on the South African retail banking sector by assessing whether the usage of these programmes has had a direct influence on customer satisfaction, perceived service quality, brand reputation, and ultimately loyalty towards the bank. The methodology used a self-administered questionnaire and data was collected from 220 participants who have an active bank account in South Africa and are currently making use of their bank loyalty programme. The study tested eight hypotheses using the Structural Equation Modelling (SEM).The software used was the SPSS version 21 and Amos version 21 for analysis. The findings of the study reveal that loyalty programmes have a positive influence on service quality and customer satisfaction. This study contributes to the literature on loyalty programmes in the banking sector. It can assist marketers in developing sound loyalty programmes aimed at the banking sector. A discussion on the limitations and directions on future research is provided
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (Strategic Marketing), 2021
Keywords: Loyalty programme; Brand reputation; Service quality; SDG-8: Decent work and economic growth